Survey Of Natural Distribution Of Black Yeasts In Malaysia With Special Emphasize On Exophiala Dermatitidis - Jayaram, Mehalene (2019)
Black yeasts are ecologically remarkable as they can live in extreme, unusual and toxic environments. Exophiala dermatitidis, a human opportunistic pathogen was previously reported to be isolated from sauna facilities, oak sleepers of railway ties, faeces of frugivorous birds and bats, land contaminated with waste petrol hydrocarbons and dishwashers worldwide. Cryptococcus neoformans, on the other hand, was isolated from tree trunk hollows, Eucalyptus trees and faeces of birds. Both of these yeasts were frequently isolated from tropical regions of the world. As there are limited reports of environmental isolation of these black yeasts in Malaysia, their natural distribution in the environment were surveyed in this study. Forty-seven strains of Exophiala spp. and four strains of Cryptococcus spp. were isolated from various locations in Malaysia. As Exophiala spp. are dimorphic fungi, the colonies were grown under different conditions to identify the yeast and hyphal growth of the black fungi. Urea hydrolysis, DNAse test and proteinase activity were also conducted to test their physiological properties. The black yeasts were characterised by the type of conidiogenous cells, and chlamydospores produced and their identity confirmed by sequencing of the ITS region. Overall, 22 strains of E. dermatitidis were successfully identified from railway track stones (n = 5), burnt tree bark (n = 2), oil dripped soil sample (n = 5), hot spring biofilm (n = 1), tar road contaminated with petrol hydrocarbon (n = 4), pigeon droppings (n = 2), drain and deep mud of Sungai Pinang (n = 3).